The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2196/jmir.5312
|View full text |Cite
|
Sign up to set email alerts
|

How Health Care Professionals Use Social Media to Create Virtual Communities: An Integrative Review

Abstract: BackgroundPrevailing health care structures and cultures restrict intraprofessional communication, inhibiting knowledge dissemination and impacting the translation of research into practice. Virtual communities may facilitate professional networking and knowledge sharing in and between health care disciplines.ObjectivesThis study aimed to review the literature on the use of social media by health care professionals in developing virtual communities that facilitate professional networking, knowledge sharing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
198
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(227 citation statements)
references
References 134 publications
21
198
1
7
Order By: Relevance
“…This is supported by Muhammad et al (2017) who report social factors especially social interaction to be a key motivation for social media use by consumers. Social media creates the opportunities for sharing knowledge that can be major drivers of social learning, networking and building symbiotic communal relationships on the basis of mutual trust, support and altruism (Rolls et al 2016). Other drivers of effective social media engagement, such as language, lexical expression (Hilte et al 2016), and style (Sparks et al 2013), have been found to influence the building of the communal bonds and relationships that can significantly impact customers' behavioural intention (Goh et al 2013;Laroche et al 2013).…”
Section: Social Media and Acculturationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by Muhammad et al (2017) who report social factors especially social interaction to be a key motivation for social media use by consumers. Social media creates the opportunities for sharing knowledge that can be major drivers of social learning, networking and building symbiotic communal relationships on the basis of mutual trust, support and altruism (Rolls et al 2016). Other drivers of effective social media engagement, such as language, lexical expression (Hilte et al 2016), and style (Sparks et al 2013), have been found to influence the building of the communal bonds and relationships that can significantly impact customers' behavioural intention (Goh et al 2013;Laroche et al 2013).…”
Section: Social Media and Acculturationmentioning
confidence: 99%
“…An original contribution of the present study is the finding that the language preferences and purchase intentions that are exhibited in social networking are key forces in whether the individual chooses to consume products and services that are associated with their heritage cultures or that of the host country. Social networking also creates social relationships by providing tools with which to engage in social interactions (e.g., photo-sharing on Facebook) (Rolls et al 2016). …”
Section: Enculturation and Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they use online physician communities more so than other platforms when conducting business on social media [8,11,16]. Two leading HCP specific communities include Sermo and Doximity [11].…”
Section: Social Media Use and Healthcarementioning
confidence: 99%
“…Una de las tendencias claramente señalada por estos trabajos es el uso creciente de las redes sociales en el ámbito sanitario (Green y Hope, 2010;Rolls et al, 2016). Así, por ejemplo, los datos más recientes muestran que más de un 60% de la población española recurre a internet para buscar información sobre salud y que un 20% usa las redes sociales con ese fin (ONTSI, 2016).…”
Section: Palabras Claveunclassified